2023
DOI: 10.1111/eth.13418
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal altruism in Norway rats

Sacha C. Engelhardt,
Michael Taborsky

Abstract: Reciprocal altruism has been proposed to generate evolutionarily stable levels of cooperation, but empirical evidence in non‐human animals is contentious. A series of experimental studies on Norway rats revealed that these animals reciprocate received help by using decision rules characterising direct and generalized reciprocity. The direct reciprocity decision rule states that individuals should help someone who previously helped them, whereas the generalized reciprocity decision rule implies that individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 176 publications
0
11
0
Order By: Relevance
“…Norway rats represent a unique model system to study the behavioural mechanisms underlying reciprocal cooperation [ 74 76 ]. Previous studies showed that wild-type Norway rats return more help to partners that had provided more benefit to them before [ 25 ], and to partners that were food-deprived or in poor body condition [ 2 , 18 ], which can lead to enhanced begging for help [ 19 , 40 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Norway rats represent a unique model system to study the behavioural mechanisms underlying reciprocal cooperation [ 74 76 ]. Previous studies showed that wild-type Norway rats return more help to partners that had provided more benefit to them before [ 25 ], and to partners that were food-deprived or in poor body condition [ 2 , 18 ], which can lead to enhanced begging for help [ 19 , 40 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors argue that rather than an explicit understanding of cost-benefit calculations, there are less cognitively demanding mechanisms such as emotions underlying thar's reciprocal actions (reviewed in Schino & Aureli, 2010;Schweinfurth & Call, 2019a). Second, a meta-analysis on foodprovisioning in Norway rats (Rattus norvegicus) showed that rats share food readily and reciprocally with others (Engelhardt & Taborsky, 2024). The rats help conspecifics who helped them in the past, following a 'You helped me, so I help you' rule.…”
Section: Interdisciplinary Perspectives On the Principle Of Reciproca...mentioning
confidence: 99%
“…Direct reciprocity was reported across several taxa, including mammals [28,29,[56][57][58][59][60][61][62] (e.g. vampire bats, Desmodus rotundus [57,58] and Norway rats, Rattus norvegicus [29,[59][60][61][63][64][65]), birds [20,21], fishes [54,55], and microorganisms [66,67]. Generalized reciprocity was reported in humans [68,69], female Norway rats [60,64,70], dogs, Canis familiaris [71], capuchin monkeys, Sapajus apella [72], however generalized reciprocity was not supported in male Norway rats [64,73], long-tailed macaques, Macaca fascicularis [74] and in vampire bats [57].…”
Section: Introductionmentioning
confidence: 99%
“…vampire bats, Desmodus rotundus [57,58] and Norway rats, Rattus norvegicus [29,[59][60][61][63][64][65]), birds [20,21], fishes [54,55], and microorganisms [66,67]. Generalized reciprocity was reported in humans [68,69], female Norway rats [60,64,70], dogs, Canis familiaris [71], capuchin monkeys, Sapajus apella [72], however generalized reciprocity was not supported in male Norway rats [64,73], long-tailed macaques, Macaca fascicularis [74] and in vampire bats [57]. Generalized reciprocity is also known as upstream tit-for-tat [47], upstream indirect reciprocity [75], upstream reciprocity [76], pay it forward [77][78][79], and serial reciprocity [80].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation